PENGARUH UKURAN PERUSAHAAN DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2016-2020 - Asriati, Novia Aisah; Tripalupi, Ramadhani Irma; Alifa, Nabiela Rizki (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine the effect of firm size and audit committee on tax avoidance. In this study, tax avoidance is measured using the Effective Tax Rate (ETR), which is the tax burden divided by profit before tax. The sample in this study was Islamic commercial banks in Indonesia for the 2016-2020 period, which amounted to 7 banks with a period of 5 years resulting in 35 data. The method used is quantitative and sampling using purposive sampling technique. The analysis technique used is multiple linear regression analysis. The results showed that the size of the company and the audit committee had no effect on tax avoidance.